Optimal temperature for normal human skin fibroblast proliferation and glucose uptake, an in vitro study - Sunardi Radiono, Yohanes Widodo, DeviArtami Susetiati, LailyNoorQomariah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Devi Artami Susetiati, Laily Noor Qomariah, Sunardi Radiono,Yohanes Widodo Wirohadidjojo -Optimal temperature for normal human skin fibroblast proliferation and glucose uptake; In vitro study Background: Wrinkles is caused by a decrease in collagen synthesis and an increase in collagen degradation. Collagen synthesis depends on fibroblast proliferation. Collagen synthesis needsglucose, so that collagen synthesis may be expressed by the increase in glucose uptake. Skin rejuvenation with heating may increase the collagen synthesis. The effect of short-term heating and optimal temperature on fibroblast proliferation and glucose uptake has not yet been defined. Objective: This study was aimed to determine the optimal temperature of short-term heating for normal human skin fibroblasts proliferation and glucose uptake. Methods: A simple experimental study was conducted on 3rd passage subculture of normal human skin fibroblasts culture, isolated from 2 patients. Normal human skin fibroblasts with complete DMEM were classified into 5 groups, and then heated for a minute with thermocycler-machine at 36°C, 46°C, 56°C, 66°C, and 72 °C. Those cells were incubated for 7 days in complete DMEM and subsequently fibroblasts proliferation was measured by MTT -assay. Glucose uptake was measured by glucometer Medisafe- Terumo. The differences in glucose uptake and fibroblasts proliferation were analyzed with one-way Anova. Result: Optimal temperature for fibroblasts proliferation was 46°C, and 66°C for collagen synthesis. Conclusion: Skin rejuvenation based on heating could be performed at two different temperatures, each cycle consisted of 66°C on first heating, and seven days later, at 46°C on second heating.